Chemical and Physical Properties of African Catfish (Clarias gariepinus) Fillet Following Prolonged Feeding with Insect Meal-Based Diets - Askale Gebremichael; András Szabó; Zsuzsanna J. Sándor; Zoltán Nagy; Omeralfaroug Ali; Balázs Kucska (Aquaculture Nutrition)
A 25-week experiment was undertaken to explore the effect of partial replacement of dietary fishmeal (FM) with black soldier fly meal (Hermetia illucens) (BS), mealworm meal (Tenebrio molitor) (MW), and a 1 : 1 mixture of both insect meals (BSMW) on fillet quality in African catfish (Clarias gariepinus). A total of 96 fish with an average initial body weight of 248 ± 28 g were stocked into a recirculating aquaculture system and fed in four different dietary groups (control, BS, MW, and BSMW). No mortality was recorded in any of the groups. At the end of the feeding period, 24 fish (n = 6 for each treatment, weight between 690 and 822 g) were used for analysis. There was no alteration in filleting yield or other slaughter indices within experimental groups, except the hepatosomatic index. Among quality attributes, pH 24 hr postmortem exhibited a significant difference (p<0.05). In respect of the fatty acid profile, the n-6/n-3 ratio ranged between 1.17 and 1.40 but was not significantly modified by the partial replacement of FM. Similarly, the proximate composition of the fillets was not significantly different between the control and experimental diet groups. The ratio of polyunsaturated fatty acid to saturated fatty acids ranged between 0.67 and 0.79 in the fillets, without significant differences between groups. The atherogenic index was increased in the BS group, as compared to the others; however, the thrombogenicity index of fillets was not significantly affected. Similarly, the conventional quality traits of the fillet, such as cooking, drip, and thawing losses, did not differ within treatments. This study demonstrates that the dietary inclusion of black soldier fly and/or mealworm meals used for African catfish at the tested inclusion level has negligible impact on fillet properties.